A Node Rating Based Sharding Scheme for Blockchain - Wang, Jianrong; Zhou, Yangyifan; Li, Xuewei; Xu, Tianyi; Qiu, Tie (2019 IEEE 25th International Conference on Parallel and Distributed Systems (ICPADS), 2019)
The incumbent sharding schemes usually assign the nodes to different committees randomly to meet the demands of security and efficiency at the same time. For example, Elastico protocol obtains a random value by letting the node perform proof of work, and then uses this value for sharding. However, the strategy of random sharding ignores the objective differences between nodes, causing performance gaps between different committees in blockchain. This creates a bottleneck in the transaction throughput of the blockchain. In the paper, we propose a node rating based sharding scheme for blockchain system called NRSS. The key idea of NRSS is to evaluate nodes in the network by both the speeds and results of transactions verification before, and then assign them into different committees by balancing the score to reduce the performance gap between committees and increase the speed of transaction process. We implement NRSS in a local blockchain system, and the experiment results show that NRSS can increase the sharding effect of a blockchain, with an average throughput increase of 32.2% in the simulation environment where the node performance difference is up to 75%, depending on the number of nodes in the committee that are preset in the blockchain.